Lifetime employment, tobacco use, and alcohol consumption trajectories and cardiovascular diseases in old age. (March 2021) - Madero-Cabib, Ignacio; Azar, Ariel; Bambs, Claudia
Abstract: Despite the great advances of life course epidemiology studies during the last decade in understanding the general health effects of employment trajectories, research has yet to evaluate the effects of employment trajectories along with other major risk factors, such as tobacco and alcohol consumption, on cardiovascular diseases (CVDs)—the main cause of deaths worldwide. This is highly relevant, since health advantages in one domain (e.g., being a permanent formal full-time worker) may offset health disadvantages in other domains (e.g., being a regular smoker or alcohol consumer); conversely, disadvantages in both domains may interact, leading to even greater health risks. Considering these knowledge gaps, this research has two main objectives: (1) to reconstruct simultaneous employment, tobacco use, and alcohol consumption trajectories over the life course (from birth to old age) and (2) to measure the association between these trajectories and CVD in old age. Drawing on a rich and comprehensive life history dataset and using multichannel sequence and regression analyses, we analyzed a cohort of individuals aged 65–75 in Chile, a Latin American country with high social inequalities and scarce research on this matter. Our study shows that following a trajectory of formal employment together with no tobacco and alcohol use reduces CVD risk by 36 percentage points relative to a similar employment trajectory but with regular tobacco and alcohol use. Even with an employment trajectory characterized by constant informal employment or permanent inactivity, a life course free of regular tobacco and alcohol use shows protective effects against CVD. This study stresses the importance of health policies that consider CVD as a condition that strongly depends on individual experiences in multiple life domains and across different life stages. Highlights: First study to analyze effects of simultaneous trajectories of employment-tobacco-alcohol on CVDs. Formal employment with no alcohol/tobacco use has highest protective effect against CVDs. No alcohol/tobacco use remains protective in the presence of informal work or inactivity. Formal employment does not mitigate high CVD risk of regular alcohol/tobacco users. A life course approach for health policies on CVD prevention is crucial.